Development of chimeric Nanobody-Granzyme B functionalized ferritin nanoparticles for precise tumor therapy - Baijin Xia; Huolun Feng; Xinmiao Jiang; Jialing Guo; Keming Lin; Wenxing Zhang; Fan Xing; Lixue Cao; Yong Li; Hui Zhang; Xu Zhang; Wenyu Li; et al. (Pharmacological Research)
T-cell lymphomas (TCLs) are heterogeneous malignancies with limited treatment options and poor outcomes. The efficacy of traditional T-cell therapies, including chimeric antigen receptor (CAR) T cells, is often constrained by immunosuppressive factors and the tumor microenvironment. On the other hand, although direct Granzyme B (GrB) administration can effectively induce tumor cell apoptosis, it lacks universal tumor targeting and efficient cellular entry mechanisms. To address these limitations, we developed a novel nanoparticle-based therapy for the precise targeting of TCL tumor cells and the delivery of GrB. We fused nanobody (Nb) targeting CD30 and CD5 with GrB and coupled them to human ferritin (h-HFn) using the Gv/Sd system, creating a novel therapeutic nanoparticle named BiCD30/5-GF, which specifically targets CD30 and CD5 receptors on TCL tumor cells. The Nb-GrB conjugation enhances tumor targeting, while a Gv/Sd linker coupled to h-HFn further improves cellular transport and targeting. Additionally, the multimerization of GrB enhances its effectiveness. These nanoparticles demonstrated superior binding affinity and cytotoxicity in vitro compared to conventional treatments. In vivo studies on tumor-bearing mice showed significant tumor suppression and prolonged survival following treatment with BiCD30/5-GF nanoparticles. We also extended similar nanoparticle strategies for gastric cancer therapy, targeting FGFR4-expressing tumor cells. Our findings highlight the potential of engineered nanoparticles as effective and targeted therapeutic agents across various tumor types, offering promising prospects for clinical translation in cancer treatment.